Herbivore performance and plant defense after sequential attacks by inducing and suppressing herbivores. (30th August 2017) - de Oliveira, Elisa Faria; Pallini, Angelo; Janssen, Arne
Abstract: It is well known that herbivore‐induced plant defenses alter host plant quality and can affect the behavior and performance of later arriving herbivores. Effects of sequential attacks by herbivores that either suppress or induce plant defenses are less well studied. We sequentially infested leaves of tomato plants with a strain of the phytophagous spider mite Tetranychus urticae that induces plant defenses and the closely related Tetranychus evansi, which suppresses plant defenses. Plant quality was quantified through oviposition of both spider mite species and by measuring proteinase inhibitor activity using plant material that had been sequentially attacked by both herbivore species. Spider‐mite oviposition data show that T. evansi could suppress an earlier induction of plant defenses by T. urticae, and T. urticae could induce defenses in plants previously attacked by T. evansi in 1 day. Longer attacks by the second species did not result in further changes in oviposition. Proteinase inhibitor activity levels showed that T. evansi suppressed the high activity levels induced by T. urticae to constitutive levels in 1 day, and further suppressed activity to levels similar to those in plants attacked by T. evansi alone. Attacks by T. urticae induced proteinase inhibitor activity in plants previously attacked by T. evansi, eventually to similar levels as induced by T. urticae alone. Hence, plant quality and plant defenses were significantly affected by sequential attacks and the order of attack does not affect subsequent performance, but does affect proteinase inhibitor activity levels. Based on our results, we discuss the evolution of suppression of plant defenses.